2022
DOI: 10.1155/2022/8071234
|View full text |Cite
|
Sign up to set email alerts
|

Th22 Cells/IL-22 Serves as a Protumor Regulator to Drive Poor Prognosis through the JAK-STAT3/MAPK/AKT Signaling Pathway in Non-Small-Cell Lung Cancer

Abstract: The interaction of immune cells and cytokines in the tumor microenvironment affects the development and prognosis of tumors with an unclear potential regulatory mechanism. Recent studies have elucidated the protumor role of Th22 cells and its lineage-specific cytokine IL-22 in different human cancers. The present study is aimed at investigating the biological effect of Th22 cells/IL-22 and its molecular mechanism in the pathogenesis process of non-small-cell lung cancer (NSCLC). It was initially found that Th2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“… 2021 ; Yao et al. 2022 ). To investigate whether IL-22 is involved in signal transduction in gefitinib-resistant PC9/GR and H1975 cells, we stimulated these NSCLC cells with exogenously added IL-22, at a 50 ng/mL concentration and measured the p-STAT3 and p-AKT protein levels 10 and 30 min after stimulation.…”
Section: Resultsmentioning
confidence: 99%
“… 2021 ; Yao et al. 2022 ). To investigate whether IL-22 is involved in signal transduction in gefitinib-resistant PC9/GR and H1975 cells, we stimulated these NSCLC cells with exogenously added IL-22, at a 50 ng/mL concentration and measured the p-STAT3 and p-AKT protein levels 10 and 30 min after stimulation.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that the IL-22/ JAK2-STAT3 signaling pathway is activated in the progression of multiple diseases. 21,35 STAT3 functions as a key signal transduction molecule in many inflammatory diseases. 36 Suzuki et al 37 and Chen et al 38 confirmed that the JAK2-STAT3 pathway was activated in a rat model of IVD degeneration and STAT3 was highly expressed in the IVD tissue, similar to our results.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 In recent studies, IL-22 was found to activate the JAK2-STAT3 signaling pathway both in vitro and in vivo. 20,21 However, to our knowledge, no study has focused on the IL-22/JAK2-STAT3 signaling pathway in IVD degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…So far, Th22 cells and their main signature, cytokine IL-22, have been associated with tumor progression in patients with hepatocellular carcinoma [ 148 ], colon cancer [ 149 ], lung cancer [ 150 , 151 ], gastric cancer [ 152 ], and ovarian cancer [ 153 ], among others. This is probably due to the effect of IL-22, which has been shown to inhibit apoptosis and promote tumor cell proliferation, angiogenesis, migration, epithelial-to-mesenchymal transition, and metastasis [ 148 , 151 , 154 , 155 , 156 , 157 , 158 ].…”
Section: Th22 Cellsmentioning
confidence: 99%